Cover Picture: Polarity control and residual strain in ZnO epilayers grown by molecular beam epitaxy on (0001) GaN/sapphire (Phys. Status Solidi RRL 9/2016). Issue 9 (September 2016) - Ullah, Md. Barkat; Avrutin, Vitaliy; Li, Si Qian; Das, Saikat; Monavarian, Morteza; Toporkov, Mykyta; Özgür, Ümit; Ruterana, Pierre; Morkoç, Hadis
Abstract : No abstract is available for this article. Abstract : Ullah et al. (pp. 682–686 ) report on the polarity control of ZnO grown by plasma assisted molecular beam epitaxy on (0001) GaN/sapphire template simply via the oxygen‐to‐Zn (VI/II) ratio during nucleation growth at 300 °C. The authors have demonstrated that ZnO polarity can be inverted, thus O‐polar ZnO can be grown even if the (0001)GaN surface is kept under continuous Zn beam exposure prior to the nucleation growth. Following the Zn pre‐exposure, ZnO nucleated with VI/II ratio below 1.5 showed Zn‐polarity and those nucleated with VI/II ratios above 1.5 exhibited O‐polarity. Scanning tunneling electron microscopy (STEM) imaging reveals that polarity inversion takes place without formation of any vertical inversion domain and within one monolayer of presumably non‐stoichiometric GaO x at the interface. A direct correlation between polarity and residual strain sign was found. Zn‐polar ZnO were under tensile biaxial strain whereas the O‐polar material showed compressive strain. Moreover, the amount of strain varied linearly with the VI/II ratio used during low‐temperature nucleation growth.